P459 High inadequate surveillance rates in colitis-associated advanced neoplasia: a multicenter retrospective cohort study. (21st January 2022) - Te Groen, M; Derks, M E; Peters, C P; Dijkstra, G; De Vries, A C; Römkens, T E; Horjus, C S; De Boer, N K; De Jong, M E; Nagtegaal, I D; Derikx, L A; Hoentjen, F
Abstract: Background: Although colorectal cancer (CRC) surveillance is embedded in IBD practice, a subset of patients still develops advanced neoplasia (AN; high-grade dysplasia (HGD) and/or CRC). We aimed to determine the most plausible explanations for AN in IBD patients through assessment of inadequate surveillance. Methods: A search of the nationwide histopathology registry of the Netherlands (PALGA) was used to identify IBD patients with AN in seven hospitals. Patients with ulcerative colitis (UC), Crohn's disease (CD), or IBD-unclassified (IBD-U) from 1 January 1991 until 1 October 2020 were eligible for inclusion. Exclusion criteria comprised familial CRC or AN prior to IBD diagnosis. A root-cause analysis based on the World Endoscopy Organizations' recommendations was performed to determine inadequate surveillance prior to the first AN, including lack of cecal intubation, insufficient bowel preparation (BBPS<6 or according to colonoscopy report) and active endoscopic inflammation. Interval inadequacy was assessed according to most recent BSG guideline including a six month margin. Associations were assessed with a binary regression model. Results: We included 179 patients with AN (figure 1). Of these, 22 patients (12.3%) were diagnosed with AN before surveillance was indicated. Inadequate surveillance was present in 122 patients (68.2%, n=50 HGD, n=72 CRC), of whom 47 patients (26.3%) did not receive any surveillance colonoscopy before AN diagnosis. A delayed surveillance interval was identified in 44 patients (24.6%), with a median deviation from surveillance recommendations of 19.0 months (IQR 9.5–28.5 months). Furthermore, 56 patients (31.3%) had active inflammation, three had insufficient bowel preparation, and two patients had an incomplete colonoscopy. Younger age at diagnosis (annual OR 0.96, 95% CI 0.94–0.98, p<0.01) and post-inflammatory polyps (OR 2.14 95% CI 1.06–4.32, p=0.03) were independently associated with inadequate surveillance. By contrast, prior indefinite for dysplasia or low-grade dysplasia was associated with adequate surveillance (OR 0.36, 95% CI 0.17–0.76, p<0.01). Finally, 35 patients (19.6%) had interval or surveillance AN despite adequate surveillance (diagnosed during a diagnostic procedure or surveillance colonoscopy, respectively). Figure 1. Root-cause analysis flowchart Conclusion: The majority of IBD patients with AN in our cohort had prior inadequate surveillance. This observation underlines the importance of adequate surveillance and guideline adherence.